Is Greulich-Pyle age estimation applicable for determining maturation in male Africans? - Kundisai Dembetembe; Alan Morris (South African Journal of Science, 2012)
Skeletal age estimation as a means of assessing development and skeletal maturation in children and adolescents is of great importance for clinical and forensic purposes. The skeletal age of a test population is estimated by comparison with established standards, the most common standards being those in the Radiographic atlas of skeletal development of the hand and wrist published by Greulich and Pyle in 1959. These standards are based on the assumption that skeletal maturity in male individuals is attained by the chronological age of 19 years. Although they have been widely tested, the applicability of these standards to contemporary populations has yet to be tested on a population of African biological origin living in South Africa. We therefore estimated the skeletal age of 131 male Africans aged between 13 and 21 years, using the Greulich-Pyle method which we applied to pre-existing hand-wrist radiographs. Estimated skeletal age was compared to the known chronological age for each radiograph. Skeletal age was on average approximately 6 months younger than chronological age. The Greulich-Pyle method underestimated skeletal age for approximately 74%of the sample and overestimated skeletal age for 26%of the sample. Skeletal maturity as characterised by complete epiphyseal fusion occurred approximately 2.1 years later than Greulich and Pyle's estimate of 19 years. Thus skeletal maturation was still in progress in a large proportion of the 20- and 21-year-old individuals in our study. The Greulich-Pyle method showed high precision but low accuracy and was therefore not directly applicable to African male individuals. Formulation of skeletal age estimation standards specific to South African populations is therefore recommended.